Использование гибридных энергогенерирующих узлов в "умных" сетях - Червоненко, Иван Игоревич; Кулешов, Владислав Сергеевич; Кулешова, Кристина Владимировна (НТУ "ХПИ", 2017)
Проблема обеспечения надежного и бесперебойного питания потребителей, питающихся от электростанций, которые работают на возобновляемых источниках энергии, очень актуальна. В данной статье проведен анализ мирового опыта по созданию гибридных энергогенерирующих узлов, работающих на возобновляемых источниках энергии. Благодаря разработанной балансовой модели энергоузла, дана оценка возможности строительства гибридных электростанций в условиях Востока Украины, и даны рекомендации по применению такого рода источников электроснабжения в структуре "умных" сетей с распределенной генерацией.

Reliable and uninterrupted power supply of consumers from electric power stations on renewable energy sources, such as solar power plants and wind power plants, are the task of current interest. Common using of solar power plants and wind power plants makes it possible to solve this problem. The article analyzes the worldwide experience in the design and construction of such hybrid power plants. A lot of attention in these studies is given to accumulation of electric energy for improving the reliability of individual power consumers, who receive the energy only from hybrid power hub. In this study we are estimating the possibility for hybrid energy hubs creation in the eastern part of Ukraine with allowance of seasonal fluctuations in power generation and the influence of meteorological factors on the energy generation. The model makes it possible to determine the capacity of power plants which are the part of an energy hub and choose there optimal configuration. It was considered the possibility of integration of the energy hubs in smart networks for improving the power supply reliability as an alternative energy storage. It was proved the feasibility of solar power plants and wind power plants co-operation in the hybrid power hubs. In the further research it is necessary to determine the optimal capacity of solar power plant, wind power plant and accumulating storage power plant in usage as a part of energy hub.
Using hybrid power generating units in "smart" networks
Keywords: солнечная электростанция; ветроэлектростанция; гидроаккумулирующая электростанция; график нагрузки; аккумулирование энергии; solar power plant; wind power plant; pumped hydro storage; load curve